Nilai Guna IP Webcam Sebagai Alat Bantu Pemeriksaan Bawah Kolong Kendaraan Bermotor - Shofiah, Siti; Griyo Arti, Tri; Gunawan, Gunawan (Pusat Penelitian dan Pengabdian Masyarakat (P3M), 2022)
Under vehicle inspection is part of the vehicle inspection process and is the most important part of the vehicle because almost 80% of the most important parts of the vehicle cannot be seen directly under the vehicle. Observation of the vehicle with the help of IP Webcam with a qualitative descriptive approach. The equipment used in this study consisted of motor vehicles to be tested, Android phones handheld cameras, laptops/computers, monitors and HDMI/VGA cables, wireless/WiFi, printers. Processing of graded data with hypothesized mean. The results of the study show that an inspector can provide information about damage audio-visually and the vehicle owner can see it from the screen without having to go under the vehicle. Then 6 categories of utility values ​​were evaluated, indications of need, comfort, appearance, time to use an IP web camera at a high value/scale were obtained. Meanwhile, satisfaction and suitability on the value/moderate scale. Therefore, it can be concluded that the use of an IP web camera as a vehicle inspection tool has been successful.